Histopathological analysis of the skin of renal transplant recipients submitted to three different immunosuppression regimens - Maria Victória Quaresma; Luiz Sergio Azevedo; Elias David-Neto; Mírian Nacagami Sotto (Anais Brasileiros de Dermatologia)
Abstract Background: Renal transplant recipients (RTRs) use a combination of immunosuppressive agents: a corticosteroid; a calcineurin inhibitor (cyclosporine or tacrolimus) and an antimetabolic agent (azathioprine [AZA] or a mycophenolic acid precursor [MPA] - Mycophenolate mofetil or sodium) or an mTOR inhibitor (mTORi) - sirolimus or everolimus. These treatments increase the incidence of various neoplasms, especially non-melanoma skin cancers (NMSCs). Objectives: To evaluate the histopathological alterations in the skin of the RTRs under three different immunosuppressive regimens: one mTORi (sirolimus or everolimus); or one antimetabolic agent (MPA or AZA), comparing them by groups and with healthy controls. Methods: This was a cross-sectional comparative study of 30 patients selected from the Renal Transplant Service and divided into three groups: mTORi (n = 10), MPA (n = 10), and AZA (n = 10). The control group consisted of 10 immunocompetent non-transplanted volunteers. All RTRs were using tacrolimus and prednisone. Each participant underwent two biopsies of intact skin: one in a sun-protected and another in a sun-exposed area. The specimens were analyzed without previous information on which group they belonged to. Results: The most significant histopathological change was thinning of the epidermis in the mTORi group, both in photoexposed and photoprotected skin. Study limitations: The study was conducted on a limited number of patients, which may influence the representativeness of the results. Conclusions: Only RTRs treated with mTORi presented interruption of epidermal proliferation. These findings help to understand the influence of these different types of immunosuppressive regimens and their subsequent potential effects on carcinogenesis.